Have we under-estimated inflation persistence before WW1? US and international evidence - Stefan Gerlach; Rebecca Stuart (Queen's University Centre for Economic History (QUCEH), 2025)
We argue that measurement error in historical price data has led researchers to erroneously believe that there was little persistence of inflation during the 19th century. Using a statistical technique that accounts for these errors, we estimate the persistence of (a) US inflation and (b) inflation in 14 other economies over the period 1842-1913. Our results indicate that persistence approximately doubles when we use this technique.
Keywords: E31; F40; N10; 330; Inflation persistence; gold standard; measurement errors; instrumental variables